The implementation of inclusive education in preschool educational institutions of Russia - Yulia A. Afanasyeva, Margarita V. Bratkova,; Komarova, Anna A.; Lazareva, Yuliya B. (Opción, 2020)
The article considers the problem of inclusion through the example of preschool educational institutions. In order to determine and scientifically substantiate structural and pedagogical conditions for the inclusion of children with impaired psychophysical development in a preschool educational institution, an ascertaining experiment was conducted in four preschool institutions. It was revealed that many problems had not been previously diagnosed for a number of reasons and, accordingly, the problem was not addressed. Most educators and parents do not know children development standards and, therefore, are not able to bring the problem into sharp focus or do not take it seriously